The Semi-Synthetic Peptide Lin-SB056-1 in Combination with EDTA Exerts Strong Antimicrobial and Antibiofilm Activity against Pseudomonas aeruginosa in Conditions Mimicking Cystic Fibrosis Sputum - Maisetta, Giuseppantonio (Int J Mol Sci, 2017)
Pseudomonas aeruginosa is a major cause of chronic lung infections in cystic fibrosis (CF) patients. The ability of the bacterium to form biofilms and the presence of a thick and stagnant mucus in the airways of CF patients largely contribute to antibiotic therapy failure and demand for new antimicrobial agents able to act in the CF environment. The present study investigated the anti-P. aeruginosa activity of lin-SB056-1, a recently described semi-synthetic antimicrobial peptide, used alone and in combination with the cation chelator ethylenediaminetetraacetic acid (EDTA). Bactericidal assays were carried out in standard culture conditions and in an artificial sputum medium (ASM) closely resembling the CF environment. Peptide’s structure and interaction with large unilamellar vesicles in media with different ionic strengths were also investigated through infrared spectroscopy. Lin-SB056-1 demonstrated fast and strong bactericidal activity against both mucoid and non-mucoid strains of P. aeruginosa in planktonic form and, in combination with EDTA, caused significant reduction of the biomass of P. aeruginosa mature biofilms. In ASM, the peptide/EDTA combination exerted a strong bactericidal effect and inhibited the formation of biofilm-like structures of P. aeruginosa. Overall, the results obtained highlight the potential of the lin-SB056-1/EDTA combination for the treatment of P. aeruginosa lung infections in CF patients.